2005
DOI: 10.1001/archopht.123.9.1215
|View full text |Cite
|
Sign up to set email alerts
|

Development of Visual Acuity in Children With Cerebral Visual Impairment

Abstract: To study the development of visual acuity in term-born children with cerebral visual impairment and a history of neonatal hypoxic-ischemic encephalopathy. Methods: We studied 19 term-born children, aged 6 months to 6 years, with moderate to severe neonatal hypoxic-ischemic encephalopathy and behaviors indicative of cerebral visual impairment. Longitudinal measures of grating acuity were obtained using preferential looking (PL) and visual evoked potential (VEP) procedures. Visual acuities at first and last visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 23 publications
4
39
0
1
Order By: Relevance
“…Similar observations in CVI were recently reported by Lowery et al [34]. Although VEPs findings in children with CVI are quite variable [31,35], and changes in parameters over a longitudinal period may not precisely represent development of visual functions in children with CVI [36], VEPs represent a method for the objective quantitative definition of vision in CVI [37].…”
Section: Discussionsupporting
confidence: 76%
“…Similar observations in CVI were recently reported by Lowery et al [34]. Although VEPs findings in children with CVI are quite variable [31,35], and changes in parameters over a longitudinal period may not precisely represent development of visual functions in children with CVI [36], VEPs represent a method for the objective quantitative definition of vision in CVI [37].…”
Section: Discussionsupporting
confidence: 76%
“…As for the amblyopia group, SPVEP acuities calculated from both methods were underestimated when the logMAR visual acuities were more than 0.50. Differences between logMAR visual acuity and SPVEP acuity were incompletely explained by differences in stimulus variables [23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…In the light of an abnormal VEP, however, the prognosis was not necessarily poor as sometimes in cases of clinical cortical vision impairment the VEP remained normal [9]. Lim et al [14] assessed visual acuity using pattern VEPs as well as preferential looking to investigate the development of visual acuity in children with cortical vision impairment. They found that both VEP and preferential looking acuity improved in children with cortical vision impairment although the increase in visual acuity was lower than in a visually normal population.…”
Section: Discussionmentioning
confidence: 99%